Organizational and Pedagogical Conditions of Development of Teacher's Creative Competence (Diversity Research: Journal of Analysis and Trends, 2023)
in this article, the active participation of future teachers in socioeconomic, cultural-educational, spiritual spheres, their social activity in the formation of responsible, passionate pedagogues with a professional-cultural point of view and their own opinion, Pedagogical bases of development of socio-pedagogical competence are covered